1995
DOI: 10.1017/s0022112095004095
|View full text |Cite
|
Sign up to set email alerts
|

Runup of solitary waves on a circular Island

Abstract: This is a study of the interactions of solitary waves climbing up a circular island. A series of large-scale laboratory experiments with waves of different incident height-to-depth ratios and different crest lengths is described. Detailed two-dimensional run-up height measurements and time histories of surface elevations around the island are presented. A numerical model based on the two-dimensional shallow-water wave equations including runup calculations was developed. Numerical model predictions agreed very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
267
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(282 citation statements)
references
References 12 publications
13
267
0
2
Order By: Relevance
“…all three numerical sets. This is consistent with previous research (e.g., Liu et al, 1995), where it is shown that bottom friction effects are minor for nonbreaking waves, and will typically alter the runup by < 0.5% of the maximum. For larger wave heights, breaking is initiated, both experimentally and numerically, near e = 0.04.…”
Section: Nonbreaking and Breaking Solitary Wave Runupsupporting
confidence: 93%
See 2 more Smart Citations
“…all three numerical sets. This is consistent with previous research (e.g., Liu et al, 1995), where it is shown that bottom friction effects are minor for nonbreaking waves, and will typically alter the runup by < 0.5% of the maximum. For larger wave heights, breaking is initiated, both experimentally and numerically, near e = 0.04.…”
Section: Nonbreaking and Breaking Solitary Wave Runupsupporting
confidence: 93%
“…The numerical results show less of a depression following the main wave than in the experiments. This deviation is consistent with other runup model tests (e.g., Liu et al, 1995;Chen et al, 2000). The agreement of Case C is especially notable, as the soliton breaks along the backside of the island as the trapped waves intersect.…”
Section: Runup On a Conical Islandsupporting
confidence: 90%
See 1 more Smart Citation
“…The COMCOT tsunami package has been extensively tested and compared with laboratory experiments for solitary waves climbing a circular island (Liu et al, 1995b). Different applications for various tsunamis events have been published including the 2004 Indian Ocean tsunami (Wang and Liu, 2006) and the 1960 Chilean tsunami recorded at Hilo, Hawaii (Liu et al, 1995a).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Nonlinear convection terms are approximated using the upwind scheme. A numerical algorithm is employed together with the leap-frog method to find the limit between the dry and wet cells tracking the shoreline movements in time and space (Liu et al, 1995b). Numerical sponge layer at the limit of the computational domain is prescribed where the amplitude of incoming waves is dampened.…”
Section: Numerical Simulationsmentioning
confidence: 99%